Cavitation-erosion-resistant martensite welding wire for water turbine runner and preparation method
By developing cavitation-resistant martensite welding wire for hydraulic turbine wheels, the problem of frequent cavitation failure of the hydraulic turbine wheel material 0Cr13Ni5Mo is solved, and the high wear resistance of the welding wire is achieved, which significantly improves the operating safety of the hydraulic turbine.
Patent Information
- Application Number
- CN202510070800.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The problem of frequent cavitation failure in the turbine wheel material 0Cr13Ni5Mo.
A cavitation-resistant martensite welding wire for turbine wheels was developed, including powder and welding skin. The powder includes Cr powder, Ni powder, Mo powder, Nb powder, W powder, C powder, B powder and Y2O3 powder according to mass percentage. The welding skin is 430 steel strips, and the core welding wire is made by a specific preparation method.
It improves the cavitation resistance of the turbine wheel, the wear resistance of the welding wire is excellent, and the wear resistance is 3.5 times to 3.74 times higher than that of the raw materials, solving the problem of cavitation failure.
Smart Images

Figure CN119733990A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and in particular relates to a cavitation-resistant martensitic welding wire for a water turbine runner. The invention also relates to a preparation method of the cavitation-resistant martensitic welding wire for the water turbine runner. Background Art
[0002] Turbine blades are key components for energy conversion in hydropower stations. They are subjected to water pressure and erosion for a long time, and are prone to cavitation damage. The surface cladding process of blade surface coating to improve the service performance of turbines has been widely studied. Common surface cladding processes include thermal spraying, laser cladding, and arc welding. The bonding strength of thermal spray coatings is low, so the service life of the coating is short. There is a metallurgical bond between the laser cladding and arc welding layers and the substrate, but laser cladding has high requirements on the structural dimensions of the cladding parts, and it is difficult to perform on-site laser cladding on conventional turbine cavitation parts. Arc cladding has strong on-site applicability and is an ideal choice for on-site repair of turbine runner cavitation parts.
[0003] The cavitation resistance of the runner surface cladding layer is closely related to the cladding material. The existing cladding materials are mainly iron-based, nickel-based and cobalt-based. Iron-based cladding materials are low in cost and are ideal materials for cladding repair of large-area turbine runners. The existing iron-based cladding materials mainly include ferrite cladding layer, martensite cladding layer and austenite cladding layer. The martensite cladding layer has high hardness and is expected to become a matching cladding material for the turbine runner material 0Cr13Ni5Mo.
[0004] Aiming at the current situation that cavitation occurs frequently in the runner material 0Cr13Ni5Mo of the water turbine, the present invention develops martensitic cladding welding materials for surface cladding repair thereof, thereby improving the operation safety of the water turbine. Summary of the invention
[0005] The first object of the present invention is to provide a cavitation-resistant martensitic welding wire for a water turbine runner, which is specifically used to solve the problem of frequent cavitation failure of a water turbine runner.
[0006] Another object of the present invention is to provide a method for preparing a cavitation-resistant martensitic welding wire for a water turbine runner.
[0007] The first technical solution adopted by the present invention is a cavitation-resistant martensitic welding wire for a turbine runner, comprising powder and welding skin, wherein the powder comprises the following components by mass percentage: Cr powder 20.0-25.0%, Ni powder 25.0-30.0%, Mo powder 5.0-8.0%, Nb powder 3.0-5.0%, W powder 3.0-5.0%, C powder 0.5-1.0%, B powder 4.0-6.0%, Y2O3 powder 0.8-1.0%, and the rest is Fe powder.
[0008] The present invention is also characterized in that: The particle size of each raw material powder is 100~200 mesh.
[0009] The weld skin is 430 steel strip with a thickness of 0.4mm and a width of 7mm.
[0010] The filling rate of flux-cored wire is controlled at 20wt% ~22wt%.
[0011] The second technical solution adopted by the present invention is a method for preparing a cavitation-resistant martensitic welding wire for a turbine runner, and the specific steps are as follows: Step 1: Weigh the following powders by mass percentage: Cr powder 20.0-25.0%, Ni powder 25.0-30.0%, Mo powder 5.0-8.0%, Nb powder 3.0-5.0%, W powder 3.0-5.0%, C powder 0.5-1.0%, B powder 4.0-6.0%, Y2O3 powder 0.8-1.0%, and the rest is Fe powder; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace for heating; the dried powder is placed in a powder mixer for thorough mixing; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use. The present invention is also characterized in that: In step 1, the particle size of each raw material powder is 100~200 mesh.
[0012] In step 2, the heating temperature in the vacuum heating furnace is 220° C. to 260° C., and the insulation time is 1 h to 3 h to remove the crystal water in the powder.
[0013] In step 2, the dried medicinal powder is placed in a powder mixer for a mixing time of 1 h to 3 h.
[0014] In step 3, the filling rate of the flux-cored wire is controlled at 20wt%~22wt%.
[0015] The beneficial effects of the present invention are: (1) The welding wire of the present invention has an excellent match of strength and toughness, and can improve the cavitation resistance of the turbine runner during service.
[0016] (2) The welding wire of the present invention is designed with martensite as the matrix structure, and achieves excellent cavitation resistance by means of multiple strengthening effects (interstitial solid solution strengthening, substitutional solid solution strengthening, and second phase strengthening): C and B are solid-dissolved in the martensite matrix to form interstitial solid solution strengthening; C and B form carbides and borides with Fe elements to form second phase strengthening; Ni, W, Nb, and Mo are solid-dissolved in the martensite matrix to form substitutional solid solution strengthening; C and W form WC, which is distributed on the martensite matrix to form second phase strengthening. When the martensite flux-cored welding wire is surfacing, the arc is stable during the surfacing process, there are no defects between the surfacing layer and the matrix, and the wear resistance is excellent.
[0017] (3) The welding wire of the present invention has a low content of alloy elements and a simple preparation method, and can be applied in large-scale engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The macrostructure morphology of the surfacing layer obtained by surfacing welding on a 0Cr13Ni5Mo substrate using the martensitic welding wire prepared in Example 2; Figure 2 The high-magnification microstructure of the surfacing layer obtained by surfacing welding on a 0Cr13Ni5Mo substrate using the martensitic welding wire prepared in Example 2; Figure 3 The friction and wear morphology of the cladding layer is shown in Figure 2 when the martensitic welding wire prepared in Example 2 is clad on a 0Cr13Ni5Mo substrate. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] The invention provides a cavitation-resistant martensitic welding wire for a turbine runner, comprising powder and welding skin, wherein the powder comprises the following components by mass percentage: 20.0-25.0% of Cr powder, 25.0-30.0% of Ni powder, 5.0-8.0% of Mo powder, 3.0-5.0% of Nb powder, 3.0-5.0% of W powder, 0.5-1.0% of C powder, 4.0-6.0% of B powder, 0.8-1.0% of Y2O3 powder, and the rest is Fe powder, and the sum of the mass percentages of the above components is 100%.
[0021] The particle size of each raw material powder is 100~200 mesh.
[0022] The weld skin is 430 steel strip with a thickness of 0.4mm and a width of 7mm.
[0023] The filling rate of flux-cored wire is controlled at 20wt% ~22wt%.
[0024] The roles and functions of the main alloy components in this martensitic welding wire are as follows: (1) Fe is the main element of flux-cored welding wire. In the present invention, by adding an appropriate amount of C, the matrix structure of the welding wire is a martensite structure. Compared with austenite and ferrite structures, martensite structure has the characteristics of higher hardness and higher strength.
[0025] (2) Cr is the main element of flux-cored welding wire. The turbine runner material 0Cr13Ni5Mo contains a certain amount of Cr, so the Cr element in the welding wire is selected to match the runner material. Cr is solid-dissolved in the martensite matrix and can improve the strength and hardness of the martensite through solid solution strengthening. Cr is a ferrite-forming element, so the addition of Cr should not be too high, otherwise a full ferrite structure will be generated, which will affect the strength and hardness of the cladding layer and is not conducive to cavitation resistance.
[0026] (3) Ni is an important additive element for flux-cored welding wire. Ni element plays a role in solid solution strengthening by dissolving in the martensite matrix. The most important role of Ni is to generate austenite structure at high temperature, thereby ensuring that austenite undergoes martensite transformation when the temperature drops, and finally generates martensite structure. A high Ni content is not good for strength and hardness, so the Ni content also needs to be controlled.
[0027] (4) W, Nb, and Mo are the main alloying elements of flux-cored welding wire. Since the atomic radius of W, Nb, and Mo is larger than that of Fe, the solid solution of W, Nb, and Mo in the Fe matrix will cause lattice distortion, thereby significantly improving the strength and hardness of the cladding layer. In addition, Nb can react with C to form NbC, and W can react with C to form WC, further improving the hardness of the cladding layer.
[0028] (5) Elements C and B are added to the flux-cored wire. Since C and B have small atomic radii, these two elements will form interstitial solid solutions when dissolved in the Fe matrix, resulting in interstitial solid solution strengthening. Although the addition amount of C and B is small, the interstitial solid solution strengthening effect of the two is very significant. In addition, C and alloying elements such as Nb and W can further generate carbides, and B and Fe can generate carbides. A variety of carbides dispersed in the martensite matrix will further improve the cavitation resistance of the cladding layer.
[0029] (6) A small amount of Y2O3 powder is added to the powder. Rare earth oxides have the function of purifying the grain boundaries and improving the bonding strength of the grain boundaries. The present invention also provides a method for preparing a cavitation-resistant martensitic welding wire for a turbine runner, and the specific steps are as follows: Step 1: Weigh the following powders by mass: 20.0-25.0% Cr powder, 25.0-30.0% Ni powder, 5.0-8.0% Mo powder, 3.0-5.0% Nb powder, 3.0-5.0% W powder, 0.5-1.0% C powder, 4.0-6.0% B powder, 0.8-1.0% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0030] In step 1, the particle size of each raw material powder is 100-200 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 220-260°C for 1-3 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1-3 hours; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 20wt%~22wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0031] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0032] Example 1 Step 1: Weigh the following powders by mass: 20.0% Cr powder, 25.0% Ni powder, 5.0% Mo powder, 3.0% Nb powder, 3.0% W powder, 0.5% C powder, 4.0% B powder, 0.8% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0033] In step 1, the particle size of each raw material powder is 100 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 220°C for 1 hour to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1 hour; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 20wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0034] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0035] The welding wire prepared in Example 1 was used to perform arc surfacing on a 0Cr13Ni5Mo substrate. The test results of the surfacing process and the surfacing layer are as follows: (1) The arc is stable during the cladding process, spatter is less, and the cladding layer is beautiful; (2) The cladding layer is mainly composed of martensite structure, which is fine and has no micro defects; (3) The microhardness of the cladding layer is 425HV0.3; (4) The friction and wear results of the cladding layer show that its wear resistance is 3.5 times higher than that of the turbine runner material 0Cr13Ni5Mo, which solves the problem of frequent cavitation failure of the turbine runner.
[0036] Example 2 Step 1: Weigh the following powders by mass: 25.0% Cr powder, 30.0% Ni powder, 8.0% Mo powder, 5.0% Nb powder, 5.0% W powder, 1.0% C powder, 6.0% B powder, 1.0% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0037] In step 1, the particle size of each raw material powder is 200 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 260°C for 3 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 3 hours; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 22wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0038] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0039] The welding wire prepared in Example 2 was used for arc surfacing on a 0Cr13Ni5Mo substrate. The test results of the surfacing process and the surfacing layer are as follows: (1) The arc is stable during the cladding process, spatter is less, and the cladding layer is beautiful; (2) The cladding layer is mainly composed of martensite structure, which is fine and has no micro defects; (3) The microhardness of the cladding layer is 431HV0.3; (4) The friction and wear results of the cladding layer show that its wear resistance is 3.6 times higher than that of the turbine runner material 0Cr13Ni5Mo, which solves the problem of frequent cavitation failure of the turbine runner.
[0040] Figure 1 The macroscopic microstructure of the surfacing layer obtained by surfacing welding on a 0Cr13Ni5Mo substrate using the martensitic welding wire prepared in Example 2. As can be seen from the figure, the surfacing layer is mainly composed of cellular dendrites, with fine structure, and no defects such as pores and inclusions are found.
[0041] Figure 2 The high-magnification microstructure of the surfacing layer obtained by surfacing welding on a 0Cr13Ni5Mo substrate using the martensitic welding wire prepared in Example 2. As can be seen from the figure, the cellular dendrites show the morphology of lath martensite under high magnification, proving that the cladding metal structure obtained by the developed welding wire meets the design requirements.
[0042] Figure 3 The friction and wear morphology of the surfacing layer is shown in the figure when the martensitic welding wire prepared in Example 2 is surfacing on a 0Cr13Ni5Mo substrate. As can be seen from the figure, the wear surface of the surfacing layer has a plowing morphology, and the wear mechanism is adhesive wear and abrasive wear.
[0043] Example 3 Step 1: Weigh the following powders by mass: 23.0% Cr powder, 27.0% Ni powder, 7.0% Mo powder, 4.0% Nb powder, 4.0% W powder, 0.8% C powder, 5.0% B powder, 0.9% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0044] In step 1, the particle size of each raw material powder is 150 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 240°C for 2 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 2 hours; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 21wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0045] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0046] The welding wire prepared in Example 3 was used to perform arc surfacing on a 0Cr13Ni5Mo substrate. The test results of the surfacing process and the surfacing layer are as follows: (1) The arc is stable during the cladding process, spatter is less, and the cladding layer is beautiful; (2) The cladding layer is mainly composed of martensite structure, which is fine and has no micro defects; (3) The microhardness of the cladding layer is 427HV0.3; (4) The friction and wear results of the cladding layer show that its wear resistance is 3.7 times higher than that of the turbine runner material 0Cr13Ni5Mo, which solves the problem of frequent cavitation failure of the turbine runner.
[0047] Example 4 Step 1: Weigh the following powders by mass: 22.0% Cr powder, 21.0% Ni powder, 6.0% Mo powder, 3.5% Nb powder, 3.5% W powder, 0.6% C powder, 4.5% B powder, 0.85% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0048] In step 1, the particle size of each raw material powder is 200 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 225°C for 1.3 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1.3 hours; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 20wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0049] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0050] The welding wire prepared in Example 4 was used to perform arc surfacing on a 0Cr13Ni5Mo substrate. The test results of the surfacing process and the surfacing layer are as follows: (1) The arc is stable during the cladding process, spatter is less, and the cladding layer is beautiful; (2) The cladding layer is mainly composed of martensite structure, which is fine and has no micro defects; (3) The microhardness of the cladding layer is 433HV0.3; (4) The friction and wear results of the cladding layer show that its wear resistance is 3.65 times higher than that of the turbine runner material 0Cr13Ni5Mo, which solves the problem of frequent cavitation failure of the turbine runner.
[0051] Example 5 Step 1: Weigh the following powders by mass: 21.0% Cr powder, 25.5% Ni powder, 5.5% Mo powder, 4.5% Nb powder, 3.1% W powder, 0.55% C powder, 4.1% B powder, 0.81% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0052] In step 1, the particle size of each raw material powder is 200 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 222° C. for 1.5 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1.5 hours; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 22wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0053] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0054] The welding wire prepared in Example 5 was used to perform arc surfacing on a 0Cr13Ni5Mo substrate. The test results of the surfacing process and the surfacing layer are as follows: (1) The arc is stable during the cladding process, spatter is less, and the cladding layer is beautiful; (2) The cladding layer is mainly composed of martensite structure, which is fine and has no micro defects; (3) The microhardness of the cladding layer is 439HV0.3; (4) The friction and wear results of the cladding layer show that its wear resistance is 3.69 times higher than that of the turbine runner material 0Cr13Ni5Mo, which solves the problem of frequent cavitation failure of the turbine runner.
[0055] Example 6 Step 1: Weigh the following powders by mass: 24.5% Cr powder, 29.0% Ni powder, 7.8% Mo powder, 4.8% Nb powder, 4.7% W powder, 0.9% C powder, 5.5% B powder, 0.95% Y2O3 powder, and the rest Fe powder. The sum of the mass percentages of the above components is 100%.
[0056] In step 1, the particle size of each raw material powder is 100 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 255°C for 2.8 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 2.7 hours; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm. In step 3, the filling rate of flux-cored wire is controlled at 20wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0057] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0058] The welding wire prepared in Example 6 was used to perform arc surfacing on a 0Cr13Ni5Mo substrate. The test results of the surfacing process and the surfacing layer are as follows: (1) The arc is stable during the cladding process, spatter is less, and the cladding layer is beautiful; (2) The cladding layer is mainly composed of martensite structure, which is fine and has no micro defects; (3) The microhardness of the cladding layer is 441HV0.3; (4) The friction and wear results of the cladding layer show that its wear resistance is 3.74 times higher than that of the turbine runner material 0Cr13Ni5Mo, which solves the problem of frequent cavitation failure of the turbine runner.
Claims
1. Cavitation-resistant martensitic welding wire for turbine runner, characterized in that: It includes powder and solder paste, wherein the powder includes the following components by mass percentage: Cr powder 20.0~25.0%, Ni powder 25.0~30.0%, Mo powder 5.0~8.0%, Nb powder 3.0~5.0%, W powder 3.0~5.0%, C powder 0.5~1.0%, B powder 4.0~6.0%, Y2O3 powder 0.8~1.0%, and the rest is Fe powder.
2. The cavitation-resistant martensitic welding wire for a water turbine runner according to claim 1, characterized in that: The particle size of each raw material powder is 100~200 mesh.
3. The cavitation-resistant martensitic welding wire for a water turbine runner according to claim 1, characterized in that: The weld skin is 430 steel strip with a thickness of 0.4mm and a width of 7mm.
4. The cavitation-resistant martensitic welding wire for a water turbine runner according to claim 1, characterized in that: The filling rate of flux-cored wire is controlled at 20wt% ~22wt%.
5. A method for preparing a cavitation-resistant martensitic welding wire for a turbine runner, characterized in that: The specific steps are as follows: Step 1: Weigh the following powders by mass percentage: Cr powder 20.0-25.0%, Ni powder 25.0-30.0%, Mo powder 5.0-8.0%, Nb powder 3.0-5.0%, W powder 3.0-5.0%, C powder 0.5-1.0%, B powder 4.0-6.0%, Y2O3 powder 0.8-1.0%, and the rest is Fe powder; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace for heating; the dried powder is placed in a powder mixer for thorough mixing; Step 3: Use 430 steel strip as welding skin, use alcohol to remove grease on the surface of 430 steel strip, and wrap the powder prepared in step 2 in 430 steel strip through flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
6. The method for preparing the cavitation-resistant martensitic welding wire for a water turbine runner according to claim 5, characterized in that: In step 1, the particle size of each raw material powder is 100~200 mesh.
7. The method for preparing the cavitation-resistant martensitic welding wire for a water turbine runner according to claim 5, characterized in that: In step 2, the heating temperature in the vacuum heating furnace is 220° C. to 260° C., and the insulation time is 1 h to 3 h to remove the crystal water in the powder.
8. The method for preparing the cavitation-resistant martensitic welding wire for a water turbine runner according to claim 5, characterized in that: In step 2, the dried medicinal powder is placed in a powder mixer for a mixing time of 1 h to 3 h.
9. The method for preparing the cavitation-resistant martensitic welding wire for a water turbine runner according to claim 5, characterized in that: In step 3, the filling rate of the flux-cored wire is controlled at 20wt%~22wt%.
Citation Information
Patent Citations
OCr13Ni5Mo steel metal flux-cored wire and preparation method thereof
CN104759788A
Metal mold flux-cored wire for 18Ni250 stainless steel and preparation method of metal mold flux-cored wire
CN107470794A
Metal flux-cored wire for welding of G520 stainless steel and 1Cr12NiW1MoV stainless steel and preparation method thereof
CN108274143A
High-strength high-toughness stainless steel electric arc welding flux-cored welding wire and preparation method thereof
CN108620766A
Flux-cored wire for welding Cr-Ni austenitic stainless steel and preparation method of flux-cored wire
CN113352021A
Cited By
W-reinforced copper-based welding wire for cavitation resistance of water turbine, preparation method and surfacing method
CN120347424A
Iron-based welding wire for resisting cavitation damage of turbine runner, preparation method and surfacing method
CN120362789A
Iron-based welding wire for anti-cavitation damage of turbine runner, preparation method and surfacing method
CN120362789B
Iron-based welding wire and method for austenitic stainless steel / carbon steel composite pipe CMT welding
CN121848017A
Iron-based welding wire for austenitic stainless steel / carbon steel clad pipe cmt welding and method
CN121848017B